The anxiety of the question between body and soul In two novels The Idiot by (Dostoyevsky) and Alzaman Almohesh by (Haider Haider). A comparative study - إبراهيم, حلا; عيد محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research traces the movement of fictional characters and distinguishes their fall under the authority of positions that conflict between their existence and harmony with their reality, and between their essence and their return to the sources of themselves, so these positions lose their significant compass. So the character stands in a position of bewilderment, anxiety, wanting to find reassuring answers, searching for balance and achieving a complete and satisfactory perception of the form of his existence. The emotions of the fictional characters in these situations range between fully responding to the authority of the situation and being trapped in it, so we see the materialistic tendency overpowering them and robbing them of their spirituality and humanity, and trying to search and think to understand human nature and provide them with satisfactory answers to their eternal question about the secret of being, and how man exists and his purpose.